2018
DOI: 10.1186/s13058-018-1029-4
|View full text |Cite
|
Sign up to set email alerts
|

Obesity promotes the expansion of metastasis-initiating cells in breast cancer

Abstract: BackgroundObesity is a strong predictor of poor prognosis in breast cancer, especially in postmenopausal women. In particular, tumors in obese patients tend to seed more distant metastases, although the biology behind this observation remains poorly understood.MethodsTo elucidate the effects of the obese microenvironment on metastatic spread, we ovariectomized C57BL/6 J female mice and fed them either a regular diet (RD) or a high-fat diet (HFD) to generate a postmenopausal diet-induced obesity model. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 62 publications
(64 reference statements)
6
56
5
Order By: Relevance
“…Additionally, Cowen et al (39) reported a higher body weight in female MMTV-PyMT mice on a HFD (35.7% energy from fat) compared to mice on a LFD (10% energy from fat), even after adjusting for tumor weight and tumor volume. Others reported that DIO promotes tumor growth, progression, and metastasis in animal models (40,41), specifically in breast cancer (16,17,33). In addition, poor treatment outcomes are also reported in overweight and obese breast cancer patients evident by larger tumor sizes and poor clinical outcomes (7,18,42,43) especially those treated with doxorubicin (42,44).…”
Section: Diet-induced Obesity Significantly Decreased Doxorubicin Trementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Cowen et al (39) reported a higher body weight in female MMTV-PyMT mice on a HFD (35.7% energy from fat) compared to mice on a LFD (10% energy from fat), even after adjusting for tumor weight and tumor volume. Others reported that DIO promotes tumor growth, progression, and metastasis in animal models (40,41), specifically in breast cancer (16,17,33). In addition, poor treatment outcomes are also reported in overweight and obese breast cancer patients evident by larger tumor sizes and poor clinical outcomes (7,18,42,43) especially those treated with doxorubicin (42,44).…”
Section: Diet-induced Obesity Significantly Decreased Doxorubicin Trementioning
confidence: 99%
“…Recently, findings from cell culture and animal models identified obesity as a main contributing factor in the underlying pathophysiology implicated in the development of breast cancer chemotherapeutic drug resistance (16,17). Patients suffering from obesity and breast cancer presented with poor clinical outcomes when treated with first line adjuvant regimens such as doxorubicin (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their isolation in the late 1940s, characterization of hormonal receptors and classification of EO771 line remains controversial. Indeed, its classification diverges according to the authors, which is considered as triple negative in 10 publications 6,12,16‐23 and as ERα+ in 19 publications 13,24‐41 . Some authors prefer to mention the unclear status of this lineage 42,43 .…”
Section: Eo771 Cell Phenotypementioning
confidence: 99%
“…7,8 Indeed, chronic inflammation and oxidative stress creates a proper microenvironment to promote tumor growth and metastasis in an obese person. 9 Breast tissue is largely made up of adipose tissue. Therefore, the role of the adipose tissue in initiation and progression of BC has been highlighted in various studies.…”
Section: Introductionmentioning
confidence: 99%